Relevansi kurikulum merdeka dengan pendidikan pembebasan - Af’idah, Maslama Nur (Maliki Interdisciplinary Journal, 2024)
This article examines the relevance of the Merdeka Curriculum to the concept of liberation education put forward by Paulo Freire. Liberation education emphasizes dialogue, critical awareness, and active participation of students in the learning process to liberate individuals from oppressive structures. The Merdeka Curriculum, introduced by the Indonesian Ministry of Education and Culture, aims to provide flexibility in learning, emphasizing project-based learning and character development. This article shows how the Merdeka curriculum is in line with the principles of liberation education through freedom of learning, contextual learning, development of critical awareness, and the role of teachers as facilitators. Although there are challenges in its implementation, the Merdeka Curriculum has great potential to transform the Indonesian education system to be more inclusive and empowering, in line with the goals of liberatory education.